A putative exonic splicing enhancer in exon 7 of the PDHA1 gene affects splicing of adjacent exons. - Ridout, C; Keighley, P; Krywawych, S; Brown, R; Brown, G (2008)
A nonsense mutation (c.729C>A, Y243X) in exon 7 of the PDHA1 gene in a patient with pyruvate dehydrogenase deficiency results in aberrant splicing of the primary transcript with production of stable mRNAs which lack either both exons 6 and 7 or exon 7 alone. Transfection and expression of genomic constructs covering exons 5 to 8 of the mutant PDHA1 gene reproduced this aberrant splicing in vitro. The same pattern of abnormal splicing was found when a silent mutation was introduced at the same position. Both the nonsense and silent mutations alter a strong consensus site for the binding of SRp40, suggesting that they may interfere with an exonic splicing enhancer in exon 7 of the gene. However, this appears to affect splicing of not only exon 7, but also the adjacent upstream exon. The splice acceptor site of intron 5 has weak homology to the consensus sequence and this may contribute to the combined splicing defect.